Resisting proletarianisation in the subsistence sector: social reproduction of gendered and racialised classes of labour - Resende, Amanda Martinho (2023)
In a world where proletarianisation historically produces a surplus population at the margins of the capitalist mode of production (Marx, 1867), questions regarding the social reproduction of the working class arise (Vogel, 1983; Gimenez, 2019). For instance, agrarian questions of labour (Bernstein, 2006, 2010) put forward the problem of commodification of subsistence along with social differentiation between more and less dispossessed classes of labour. This fragmentation is also informed by the flipside of commodification, the ongoing importance of non-commodified relations of production, such as kinship and gender relations, as well as solidarity ties in traditional communities. In other words, the onus of social reproduction, in terms of non-monetised, non-costly for capital, reproductive labour hinges on gendered and racialised bodies. Given this context, in the first paper of this dissertation, I propose a critique of the political economy of development and its understanding of proletarianisation in the global South (and more generally, in the global North), epitomised in Lewis (1954) classic formulation, a dual economy, with its division between a subsistence sector and a capitalist sector. By doing so, I seek to understand further Marxs special commodity, labour power, the only one not reproduced capitalistically (Bhattacharya, 2017). In the second paper, I investigate the Brazilian historical experience of proletarianisation and present empirical evidence from the Agricultural and Livestock Censuses and the Quarterly National Household Sample Survey to argue that pluriactivity (Schneider, 2003), as an income diversification resistance strategy of family farmers and peasants, is articulated to gendered and racialised classes of labour.